Guarantees of family stability in the Holy Quran and the Prophet's Sunnah | ضمانات الاستقرار الأسري في القرآن الكريم والسنة النبوية (دراسة وصفية تحليلية) - Aisha Shareef (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2020)
This research was entitled Guarantees of Family Stability in the Holy Quran and the Prophet's Sunnah. I made him an introduction in which I talked about the importance of the topic and the reasons for its selection and previous studies and I divided it into three investigations and under each topic a number of demands. In the first topic about the definition of the family and its pillars and functions، and in the second topic i talked about the factors of family stability in the Holy Quran and the third topic came about the factors of stability of the family in the prophetic year of cleansing. eventually، I concluded the research with a conclusion in which the most important findings of this study were outlined with the most important recommendations. I graduated the verses and attributed them to their walls، and the hadiths came out of their thoughts and drew up a list of sources and references that they relied on in the research.